Collection of tasks for control and independent works in mathematics. Part 1: supplement to the textbook ‘Mathematics’ (for foreign students of the preparatory department of all specialities) - Kuznetsova H. A.; Voronovska L. P. (O. M. Beketov NUUE, 2025)
The collection of independent and control works in Mathematics is an appendix to the textbook “Mathematics: Study Guide: For Foreign Students of the Preparatory Department” and contains tasks for independent and control works on the first section of the textbook – “Arithmetic”.
Keywords: ARITHMETICS; Numbers and figures; Basic mathematical signs; Arithmetic operations; Divisibility of numbers; Greatest common divisor; least common multiple; Ordinary fractions; Actions with common fractions; Decimals and operations with them; Ratios; Proportions; Percentages